An activated carbon fiber-supported graphite carbon nitride for effective electro-Fenton process. (20th June 2018) - He, Zhiqiao; Chen, Jinping; Chen, Yu; Makwarimba, Chengetai Portia; Huang, Xinwen; Zhang, Shihan; Chen, Jianmeng; Song, Shuang
Abstract: Advanced oxidation processes based on the electro-Fenton process are alternative technologies for water and wastewater remediation. In the present work, an activated carbon fiber-supported graphite carbon nitride (g-C3 N4 /ACF) was prepared by a wet impregnation method, followed by calcination. The results from scanning electron microscopy and X-ray photoelectron spectroscopy demonstrated that the g-C3 N4 was successfully supported on the surface of the ACF, leading to a slight decrease in the Brunauer-Emmett-Teller surface area. In the presence of externally added Fe 2+ to the electrolyte, the g-C3 N4 /ACF used as a cathode exhibited a relatively higher activity in the electrochemical degradation of aqueous rhodamine B (RhB) compared to the ACF cathode. The effect of several experimental conditions, such as initial pH, current density, the quantity of Fe 2+ added, and the loading amounts of g-C3 N4, on the removal of total organic carbon was explored. In the range investigated, the mineralization of RhB had the most rapid progression, with an initial pH of 3.0, current density of 3.0 mA cm −2, initial Fe 2+ concentration of 0.25 mM and g-C3 N4 load of 0.03 g. The removal efficiency of total organic carbon was ∼91% after 240 min of electrolysis. In addition, the g-C3 N4 /ACF electrode was stable as evidenced by five successive cyclic tests. On the basis of quantitative measurements of iron (zero-valent iron, ferrous ion, and ferric ion) and qualitative determination of hydroxyl radicals, and with the help of electrochemical characterization in the form of linear sweep voltammetry, cyclic voltammetry and chronoamperometry, it could be concluded that the RhB mineralization proceeded via a surface process. The supported g-C3 N4 facilitated the electro-generation and adsorption of H2 O2, as well as the regeneration of ferrous ions from surface-adsorbed ferric ions. Graphical abstract: Image 1